Severity of Rhizoctonia solani on the leaves of rice and turmeric - ROY, A.K. (Indian Phytopathology, 2002)
The severity of sheath blight fungus of rice (Rhizoctonia solani] was aggravated under shade on rice but leaf blight of turmeric caused by the same fungus reduced under the same environment. Calcium contents were highest in rice leaves grown in direct sunlight and in leaves of turmeric under shade, R, solani infection on excised rice leaves supplied with calcium acetate was reduced and eliminated in calcium chloride. Calcium is implicated for resistance.